Representasi Kekerasan Dalam Drama Korea The Glory (Analisis Semiotika Roland Barthes) - Jayanti, Jetri Putri; Yanto, Yanto; Dianthi, Martha Heriniazwi (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
Violence is an act by individuals or groups that can cause victims to experience physical and non-physical pain. This study aims to analyze the representation of violence in the Korean drama The Glory committed by the cast in the Korean drama The Glory. This research uses a qualitative approach using the Roland Barthes semiotic analysis method with Sanford H. Khadis' theory of violence. Korean drama The Glory can represent 5 forms of violence according to Sanford H. Kadish's classification. In the Korean drama The Glory contains violence presented in 9 scenes contained in the scenes of the cast of this drama. Each form or type of violence represented in this drama shows a sign of denotation, connotation and myth in Roland Barthes' semiotics.